Measurement of absolute intensity of 1001 keV gamma-ray of 234mPa - Turhan, Şeref; Yücel, H.; Karadeniz, H.; Çetiner, M.A.; Demirel, H. (Journal of Radioanalytical and Nuclear Chemistry, Vol. 258, No. 2 (2003), 2003)
The 1001 keV -ray emission from 234mPa as an analytical peak has ever increasing importance in direct -ray spectrometric measurements of 238U content in samples with the development of high pure Ge detectors of larger crystal volumes and higher efficiency. In this study, -ray spectrometric measurement for the determination of the absolute intensity, P , of 1001 keV -rays of 234mPa was carried out using powdered uranium samples and a new experimental value of 0.861±0.015% for P of the 1001 keV -ray of 234mPa has been obtained. The present measured value is greater than most of the recent experimental results and the newly recommended value of 0.835±0.004% for P by 2.5 to 4%. The present result differs from the latest experimental value of 0.92±0.02% by 7%
Keywords: Measurement; absolute intensity